Center of pressure progression patterns during level walking in adolescents with idiopathic scoliosis - Gao, Chia-Chi; Chern, Jen-Suh; Chang, Chun-Ju; Lai, Po-Liang; Lung, Chi-Wen (PloS one, 2019)
The purpose of this study was to determine whether functional walking performance measured with Timed Up-and-Go (TUG) and center of pressure (CoP) progression pattern is different across adolescents with various curve severity of idiopathic scoliosis (IS). The CoP coordinates during a stance phase for self-paced level walking between adolescent with three different severities of IS (mild IS, moderate IS, and severe IS) and age-matched normal subjects were measured with foot pressure measurement. The average data of three trials were compared among groups with repeated measure analysis of variance. Results showed that the TUG was different between normal and AIS subjects, indicating use of TUG as a marker of functional walking performance in AIS is plausible but studies with larger sample size is needed before using TUG to identify AIS with different scoliosis severity. The results also showed that the CoP displacement, velocity and acceleration during a stance phase was different across groups, and with the most prominent deviations found in the moderate IS group. The medial-lateral shifting of the CoP trajectory at mid-foot regions in all IS groups deviated the most. A tendency of asymmetry in CoP progression pattern between feet in IS groups was also found. The deviation of the spine alignment in frontal plane could change the CoP progression patterns during level walking, suggesting the risk of the locomotors subjecting to abnormal loading during daily walking. Education and conservative interventions might be needed for preservation of medical outcome and prevention of back pain and/or musculoskeletal consequences later in the lives of AIS with and without surgical correction.